Pertanggungjawaban Pidana Terhadap Wanita dalam Perdagangan Narkotika (Studi Putusan No reg. 533 / Pid.Sus / 2013 / PN.TK) - Zainab Ompu Jainah (Universitas Bandar Lampung (UBL), 2016)
Narcotics is a violation of the law and violation of social norms that have been around a long time in line with the development of other crimes such as prostitution, gambling, and others. The research problem is how the criminal accountability for perpetrators of drug trafficking carried out by a woman? Juridical normative and empirical approach, the data used is qualitative analysis. Based on the research panel of judges in the trial of the case of narcotics, with No. reg. 533 / Pid.Sus / 2013 / PN.TK verdict for NUR is we Als MILA proven legally and convincingly guilty of committing a crime